ANALISIS PERBANDINGAN KINERJA KEUANGAN PT. BANK BRI DAN PT. BANK MANDIRI PERIODE TAHUN 2010-2014 DENGAN MENGGUNAKAN RASIO KEUANGAN - Loupatty, Sindie Margaretha; Pangemanan, Sifrid S.; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2018)
Company's financial performance can be seen from the aspect of financial ratios, such as LDR, CAR, ROA and ROE. The development of a company, can be seen and can be compared through the company's financial performance. This is certainly useful for investors, creditors, and owners to make profitable investment decisions. This study aims to determine the differences in financial performance of PT. Bank BRI Tbk (Bank BRI) and PT. Bank Mandiri Tbk (Bank Mandiri) by using financial ratio analysis. This research has used Independent analysis method of sample t-test. This research uses secondary data from Indonesia Stock Exchange. The result of the research shows that there are significant differences in financial performance between Bank BRI and Bank Mandiri. Suggestions for the Management should better improve the financial performance in order to attract the attention of investors, so as to maintain its predicate as a bank that has the greatest asset in Indonesia.Keywords : : LDR, CAR, ROA, and ROE